Imaging of Tumor Hypoxia With Radionuclide-Labeled Tracers for PET - Huang, Yuan; Fan, Junying; Li, Yi; Fu, Shaozhi; Chen, Yue; Wu, Jingbo (Frontiers in Oncology, 2021)
The hypoxic state in a solid tumor refers to the internal hypoxic environment that appears as the tumor volume increases (the maximum radius exceeds 180-200 microns). This state can promote angiogenesis, destroy the balance of the cell's internal environment, and lead to resistance to radiotherapy and chemotherapy, as well as poor prognostic factors such as metastasis and recurrence. Therefore, accurate quantification, mapping, and monitoring of hypoxia, targeted therapy, and improvement of tumor hypoxia are of great significance for tumor treatment and improving patient survival. Despite many years of development, PET-based hypoxia imaging is still the most widely used evaluation method. This article provides a comprehensive overview of tumor hypoxia imaging using radionuclide-labeled PET tracers. We introduced the mechanism of tumor hypoxia and the reasons leading to the poor prognosis, and more comprehensively included the past, recent and ongoing studies of PET radiotracers for tumor hypoxia imaging. At the same time, the advantages and disadvantages of mainstream methods for detecting tumor hypoxia are summarized.